Composite polishing layer, polishing pad and preparation method thereof
By adopting a composite polishing layer structure on the polishing pad, using the combination of high-hardness first polyurethane and flexible second polyurethane, the problems of fiber removal and uneven hardness of the polishing pad are solved, achieving a longer service life and a higher removal rate.
Patent Information
- Application Number
- CN202411551298.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-10-31
AI Technical Summary
Existing polishing pads are prone to fiber removal or breaking under the action of strong oxidative polishing liquid, resulting in failure of the polishing layer and uneven hardness may cause wafer scratches.
The composite polishing layer structure is adopted, wherein the first polishing layer is composed of a first polyurethane with a hardness of 95-110A, providing a high hardness porous framework; the second polishing layer is composed of a second polyurethane with a hardness of 50-70A, forming a porous polishing layer with uniform adjustable and high resilience, achieving a "soft-pack and hard" microstructure.
It enhances the stability and service life of the polishing layer, avoids wafer scratches caused by excessive hardness, and improves the elasticity and removal rate of the polishing pad.
Smart Images

Figure CN119795025A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polishing, and in particular to a composite polishing layer, a polishing pad and a preparation method thereof. Background Art
[0002] In order to obtain ultra-smooth, damage-free, micro-defect-free high-quality processing surfaces of semiconductor wafers, a variety of ultra-precision polishing methods have been proposed. Chemical mechanical polishing (CMP) is considered to be almost the only surface finishing technology that can provide global planarization for hard and brittle optoelectronic materials. It uses chemical reactions to oxidize the surface of the wafer to form a surface softening layer with lower hardness, weaker strength and smaller bonding force, and then mechanical material removal occurs through the relative movement between the polishing pad, ultra-fine abrasive particles and the wafer. Different from pure chemical or mechanical polishing methods, in CMP, by achieving a balance between chemical and mechanical actions, problems such as slow polishing speed, low surface flatness and more damage that are prone to occur in the former two methods can be avoided.
[0003] The polishing pad is a core component in the CMP process. It plays the role of storing and transporting polishing liquid and removing micro-protrusions on the surface of the wafer. Its mechanical properties, including hardness, elasticity, compressibility, as well as microstructure and surface roughness, will affect the final polishing effect of the wafer. A large number of experiments have shown that with the increase of polishing time, under the action of strong oxidizing polishing liquid, the polishing pad will undergo obvious physical changes. For the polishing layer of non-woven polishing pads, there are two main failure situations: fiber pulling out or breaking after resin wear, resulting in macroscopic "fluffing" phenomenon; polishing residue and self-wear caused by "glazing" or "smoothing" phenomenon. Among them, the failure of the former will directly lead to the end of the life of the polishing pad, and the latter can restore the rough porous surface through surface dressing or adjustment. However, since the properties of the polishing layer such as hardness and density are not uniform, and the control of the dressing device and the corresponding system parameters is still insufficient, the polishing layer will produce larger defects, resulting in scratches on the wafer surface. Therefore, it is necessary to improve the polishing layer. Summary of the invention
[0004] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the present invention provides a composite polishing layer, a polishing pad and a preparation method thereof. The composite polishing layer can enhance the resin to prevent the fiber from being pulled out prematurely, enhance the uniformity and adjustability, and ensure a high wafer removal rate while making the polishing pad have a longer service life.
[0005] To this end, a first aspect of the present invention provides a composite polishing layer, the composite polishing layer comprising a first polishing layer and a second polishing layer, wherein the second polishing layer is coated on the first polishing layer;
[0006] Wherein, the first polishing layer comprises a first polyurethane, the hardness of the first polyurethane is 95-110A, and the number average molecular weight is 3w-5w g / mol;
[0007] The second polishing layer includes a second polyurethane, and the hardness of the second polyurethane is 50-70A and the number average molecular weight is 5w-20w g / mol.
[0008] The inventor found that when the hardness of the first polyurethane is 95-110A and the number average molecular weight is 3w-5w g / mol, it indicates that the rigid segment content in the polyurethane is relatively high, and a high-hardness porous skeleton can be formed to provide strong mechanical properties. When the hardness of the second polyurethane is 50-70A and the number average molecular weight is 5w-20w g / mol, it indicates that the proportion of flexible segments in the polyurethane is relatively high, and a uniform, adjustable, and highly resilient porous polishing layer can be formed. The composite of the above two polishing layers can form a "soft-encased hard" microstructure. The first polishing layer can enhance the stability of the fiber under high shear, solve the problem of pulling off to a certain extent, and increase the service life of the polishing layer; the second polishing layer can avoid the wafer defects caused by the excessive hardness of the polishing pad; at the same time, using it for the polishing pad can increase the overall resilience, can more effectively discharge polishing debris, improve the glazing phenomenon during the polishing process to a certain extent, and maintain a high removal rate of the wafer.
[0009] According to an embodiment of the present invention, the first polyurethane is a reaction product comprising a first polyether diol, a first chain extender, a first diisocyanate, and an optional first end-capping agent;
[0010] Wherein, the number average molecular weight of the first polyether diol is 200-1000 g / mol;
[0011] and / or, the hard segment content in the first polyurethane is 45-75wt%;
[0012] And / or, the first polyether diol includes at least one of polytetramethylene glycol, polyethylene glycol, polypropylene glycol, tetramethylene glycol-propylene oxide copolymer, propylene oxide-ethylene oxide copolymer, bisphenol A polyoxyethylene ether, and bisphenol A polyoxypropylene ether;
[0013] And / or, the first chain extender is a small molecule diol or diamine; preferably includes at least one of diols and diamines; preferably aliphatic diols and / or aromatic diols; more preferably at least one of ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, hexanediol, neopentyl glycol, hydroquinone dihydroxyethyl ether, and resorcinol dihydroxyethyl ether;
[0014] and / or, the first diisocyanate includes at least one of 4,4′-diphenylmethane diisocyanate, 2,4-diphenylmethane diisocyanate, 2,2′-diphenylmethane diisocyanate, m-xylylene diisocyanate, and 1,5-naphthalene diisocyanate;
[0015] And / or, the first capping agent includes a monofunctional capping agent and / or a difunctional capping agent; preferably a monofunctional capping agent containing a hydroxyl group or an amino group; more preferably at least one of methanol, phenol, p-chlorophenol, ethanol, dibutylamine, 2-isopropylamine, isobutanol, n-butanol, amyl alcohol, isopentanol, and propanol.
[0016] According to an embodiment of the present invention, the second polyurethane is a reaction product comprising a second polyether diol, a second chain extender, a second diisocyanate, and an optional second end-capping agent;
[0017] Wherein, the number average molecular weight of the second polyether diol is 200-3000 g / mol;
[0018] And / or, the hard segment content in the second polyurethane is 5-40wt%;
[0019] And / or, the second polyether diol comprises at least one of polytetramethylene ether diol and a polyether diol using bisphenol A as an initiator;
[0020] And / or, the polyether diol using bisphenol A as an initiator includes but is not limited to at least one of bisphenol A polyoxyethylene ether and bisphenol A polyoxypropylene ether;
[0021] and / or, the molecular weight of the second chain extender is 500-2000 g / mol; preferably at least one of polyethylene glycol, polypropylene glycol, tetrahydrofuran-propylene oxide copolymer glycol, and tetrahydrofuran-ethylene oxide copolymer glycol;
[0022] and / or, the second diisocyanate comprises at least one of 4,4′-diphenylmethane diisocyanate, 2,4-diphenylmethane diisocyanate, 2,2′-diphenylmethane diisocyanate, m-xylylene diisocyanate, and 1,5-naphthalene diisocyanate;
[0023] And / or, the second capping agent includes a monofunctional capping agent and / or a difunctional capping agent; preferably a monofunctional capping agent containing a hydroxyl group or an amino group; more preferably at least one of methanol, phenol, p-chlorophenol, ethanol, dibutylamine, 2-isopropylamine, isobutanol, n-butanol, amyl alcohol, isopentanol, and propanol.
[0024] According to an embodiment of the present invention, the first polishing layer and the second polishing layer are non-foamed bodies.
[0025] A second aspect of the present invention provides a polishing pad, comprising a composite polishing layer and a non-woven fabric, wherein the composite polishing layer is the composite polishing layer described in the first aspect.
[0026] The polishing pad has high wafer removal rate and longer service life.
[0027] According to an embodiment of the present invention, the first polishing layer is coated on the non-woven fabric;
[0028] And / or, the mass proportion of the composite polishing layer in the polishing pad is 50%-70%, and the mass proportion of the non-woven fabric is 30%-50%.
[0029] The third aspect of the present invention provides a method for preparing the polishing pad according to the second aspect, the preparation method comprising:
[0030] The composite polishing layer is prepared, and the composite polishing layer is composited with the non-woven fabric to obtain the polishing pad.
[0031] According to an embodiment of the present invention, the preparation method further comprises:
[0032] The first polyether diol, the first chain extender, and the first diisocyanate are mixed to generate a first chain extension reaction to obtain a first impregnation solution;
[0033] The second polyether diol, the second chain extender and the second diisocyanate are mixed to generate a second chain extension reaction to obtain a second impregnation solution;
[0034] Immersing the nonwoven fabric in the first impregnation liquid and performing a first heat treatment to obtain a nonwoven fabric coated with a first polishing layer;
[0035] The nonwoven fabric covered with the first polishing layer is immersed in the second impregnating liquid and subjected to a second heat treatment to obtain the polishing pad.
[0036] According to an embodiment of the present invention, the preparation method further comprises:
[0037] The first polyether diol, the third chain extender, and the first diisocyanate are mixed to obtain a first mixed solution, wherein the molar ratio of isocyanate groups to hydroxyl groups in the first mixed solution is (1:1)-(1.5:1), and a first prepolymerization reaction occurs; the fourth chain extender is added to the mixed solution after the first prepolymerization reaction, such that the molar ratio of isocyanate groups to hydroxyl groups in the mixed solution after the first prepolymerization reaction is (0.85:1)-(1:1), and a first chain extension reaction occurs to obtain a first impregnation solution;
[0038] A second polyether diol and a second diisocyanate are mixed to obtain a second mixed solution, wherein the molar ratio of isocyanate groups to hydroxyl groups in the second mixed solution is (1:1)-(3:1), and a second prepolymerization reaction occurs; a second chain extender is added to the mixed solution after the second prepolymerization reaction, such that the molar ratio of isocyanate groups to hydroxyl groups in the mixed solution after the second prepolymerization reaction is (0.85:1)-(1:1), and a second chain extension reaction occurs to obtain a second impregnation solution;
[0039] Wherein, the first chain extender includes a third chain extender and a fourth chain extender, and the third chain extender and the fourth chain extender are the same or different.
[0040] According to an embodiment of the present invention, the solid content of the mixed solution after the first prepolymerization reaction is 30%-50%;
[0041] and / or, the solid content of the mixed solution after the first chain extension reaction is 25%-35%;
[0042] and / or, the solid content of the mixed solution after the second prepolymerization reaction is 30%-50%;
[0043] And / or, the solid content of the mixed solution after the second chain extension reaction is 25%-35%.
[0044] According to an embodiment of the present invention, the preparation method further comprises:
[0045] Diluting the first impregnation solution to a solid content of 8% to 20%;
[0046] And / or, the second impregnation liquid is diluted to have a solid content of 8%-20%.
[0047] According to an embodiment of the present invention, the time of the first prepolymerization reaction is 1-3h;
[0048] and / or, the temperature of the first prepolymerization reaction is 50-90° C.;
[0049] And / or, the time of the first chain extension reaction is 1-3h;
[0050] And / or, the temperature of the first chain extension reaction is 50-90°C.
[0051] According to an embodiment of the present invention, the time of the second prepolymerization reaction is 1-8h;
[0052] and / or, the temperature of the second prepolymerization reaction is 50-90° C.;
[0053] And / or, the time of the second chain extension reaction is 1-5h;
[0054] And / or, the temperature of the second chain extension reaction is 50-90°C.
[0055] According to an embodiment of the present invention, the preparation method further comprises: mixing the mixed solution after the first chain extension reaction with the first end-capping agent to obtain a first impregnation solution;
[0056] And / or, the mixed solution after the second chain extension reaction is mixed with the second end-capping agent to obtain a second impregnation solution.
[0057] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0059] Figure 1 The morphology of the nonwoven fabric in Example 1 of the present invention when it is not treated is shown;
[0060] Figure 2 shows the surface morphology of the first polishing layer in Example 1 of the present invention;
[0061] Figure 3 The surface morphology of the second polishing layer in Example 1 of the present invention is shown;
[0062] Figure 4 shows a cross-sectional morphology of the polishing pad in Example 1 of the present invention;
[0063] Figure 5 The surface morphology of the composite polishing layer after polishing with the polishing pad for 44 hours in Example 1 of the present invention is shown;
[0064] Figure 6 The surface morphology of the polishing layer after polishing for 50 hours by the polishing pad in Comparative Example 1 of the present invention is shown;
[0065] Figure 7 The surface morphology of the polishing layer after polishing with the polishing pad for 14 hours in Comparative Example 3 of the present invention is shown;
[0066] Figure 8 The profile scanning diagram of the SiC wafer processed by the polishing layer in Comparative Example 2 of the present invention is shown;
[0067] Fig. 9 The profile scan of the SiC wafer after processing for 4 hours in Comparative Example 1 of the present invention is shown. DETAILED DESCRIPTION
[0068] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.
[0069] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.
[0070] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0071] In order to make the present invention more easily understood, certain technical and scientific terms are specifically defined below. Unless otherwise clearly defined elsewhere in this document, all other technical and scientific terms used herein have the meanings commonly understood by those skilled in the art to which the present invention belongs.
[0072] In this document, the terms “include” or “comprising” are open expressions, that is, including the contents specified in the present invention but not excluding other contents.
[0073] As used herein, the terms "optionally", "optional" or "optionally" generally mean that the subsequently described event or circumstance may but need not occur, and that the description includes instances where the event or circumstance occurs and instances where it does not.
[0074] According to an embodiment of the present invention, a first aspect of the present invention provides a composite polishing layer, the composite polishing layer comprising a first polishing layer and a second polishing layer, wherein the second polishing layer is coated on the first polishing layer;
[0075] Wherein, the first polishing layer comprises a first polyurethane, the hardness of the first polyurethane is 95-110A, and the number average molecular weight is 3w-5w g / mol;
[0076] The second polishing layer includes a second polyurethane, and the hardness of the second polyurethane is 50-70A and the number average molecular weight is 5w-20w g / mol.
[0077] Thus, a rigid skeleton is constructed through the first polishing layer, the hardness and wear resistance of the polishing layer are improved, and fiber removal is improved. At the same time, a flexible second polishing layer is coated on the first polishing layer to avoid excessive hardness of the rigid skeleton, which causes wafer scratches, and increase resilience, avoid the surface glazing problem caused by the grinding debris generated during the polishing process blocking the groove pores, and ensure a high removal rate of the wafer during the polishing process. Applying it to the polishing pad also makes the polishing pad have a longer service life.
[0078] As some specific examples, the hardness of the first polyurethane may be 95A, 96A, 97A, 98A, 99A, 100A, 101A, 102A, 103A, 104A, 105A, 106A, 107A, 108A, 109A, 110A, etc. The number average molecular weight of the first polyurethane may be 3w g / mol, 3.5w g / mol, 4w g / mol, 4.5w g / mol, 5w g / mol, etc.
[0079] As some specific examples, the hardness of the second polyurethane may be 50A, 51A, 52A, 53A, 54A, 55A, 56A, 57A, 58A, 59A, 60A, 61A, 62A, 63A, 64A, 65A, 66A, 67A, 68A, 69A, 70A, etc. The number average molecular weight of the second polyurethane may be 5w g / mol, 6w g / mol, 7w g / mol, 8w g / mol, 9w g / mol, 10w g / mol, 11w g / mol, 12w g / mol, 13w g / mol, 14w g / mol, 15w g / mol, 16w g / mol, 17w g / mol, 18w g / mol, 19w g / mol, 20w g / mol, etc.
[0080] According to a specific embodiment of the present invention, the first polyurethane is a reaction product comprising a first polyether diol, a first chain extender, a first diisocyanate, and an optional first end-capping agent; wherein the number average molecular weight of the first polyether diol is 200-1000 g / mol, such as 200 g / mol, 300 g / mol, 400 g / mol, 500 g / mol, 600 g / mol, 700 g / mol, 800 g / mol, 900 g / mol, 1000 g / mol, etc. The polyether diol in the above number average molecular weight range has a high content of rigid segments, so that the prepared polyurethane has a high hardness, providing strong mechanical properties for the first polishing layer.
[0081] According to a specific embodiment of the present invention, the hard segment content in the first polyurethane is 45-75wt%. As some specific examples, the hard segment content in the first polyurethane is 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, etc. Wherein, "hard segment content" refers to the total mass proportion of small molecule chain extenders (molecular weight less than or equal to 250g / mol) and diisocyanates in the polyurethane.
[0082] According to a specific embodiment of the present invention, the first polyether diol includes but is not limited to polytetramethylene glycol, polyethylene glycol, polypropylene glycol, tetramethylene glycol-propylene oxide copolymer, propylene oxide-ethylene oxide copolymer, bisphenol A polyoxyethylene ether, and bisphenol A polyoxypropylene ether.
[0083] According to a specific embodiment of the present invention, the first chain extender is preferably a small molecule chain extender, such as a diol, a diamine, more preferably an aliphatic diol, an aromatic diol, including but not limited to ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, hydroquinone dihydroxyethyl ether, and resorcinol dihydroxyethyl ether.
[0084] According to a specific embodiment of the present invention, the first diisocyanate includes but is not limited to 4,4′-diphenylmethane diisocyanate (4,4′-MDI), 2,4-diphenylmethane diisocyanate (2,4-MDI), 2,2′-diphenylmethane diisocyanate (2,2′-MDI), meta-xylylene diisocyanate (XDI), and 1,5-naphthalene diisocyanate (NDI).
[0085] According to a specific embodiment of the present invention, the raw materials for preparing the first polyurethane may be optionally added with a first capping agent, which may be a monofunctional capping agent or a difunctional capping agent, preferably a monofunctional capping agent containing a hydroxyl group or an amino group, including but not limited to methanol, phenol, p-chlorophenol, ethanol, dibutylamine, 2-isopropylamine, isobutanol, n-butanol, amyl alcohol, isopentanol, propanol, etc.
[0086] According to a specific embodiment of the present invention, the second polyurethane is a reaction product comprising a second polyether diol, a second chain extender, a second diisocyanate, and an optional second end-capping agent; wherein the number average molecular weight of the second polyether diol is 200-3000 g / mol, such as 200 g / mol, 500 g / mol, 1000 g / mol, 1500 g / mol, 2000 g / mol, 2500 g / mol, 3000 g / mol, etc. The polyether diol in the above number average molecular weight range has a high content of soft segments, so that the prepared polyurethane has a low hardness, forming a uniform, adjustable, and highly resilient porous polishing layer.
[0087] According to a specific embodiment of the present invention, the hard segment content in the second polyurethane is 5-40wt%. As some specific examples, the hard segment content in the second polyurethane is 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt% and the like.
[0088] According to a specific embodiment of the present invention, the second polyether diol includes but is not limited to polytetramethylene ether diol and a polyether diol using bisphenol A as an initiator. The "initiator" is a starting material in the synthesis process of a polyol, which is used to initiate a polymerization reaction. Specifically, the polyether diol using bisphenol A as an initiator includes but is not limited to bisphenol A polyoxyethylene ether and bisphenol A polyoxypropylene ether.
[0089] According to a specific embodiment of the present invention, the molecular weight of the second chain extender is 500-2000 g / mol, that is, it is a flexible chain extender, and its molecular weight can be 500 g / mol, 600 g / mol, 700 g / mol, 800 g / mol, 900 g / mol, 1000 g / mol, 1100 g / mol, 1200 g / mol, 1300 g / mol, 1400 g / mol, 1500 g / mol, 1600 g / mol, 1700 g / mol, 1800 g / mol, 1900 g / mol, 2000 g / mol, etc. Specifically including but not limited to polyethylene glycol, polypropylene glycol, tetrahydrofuran-propylene oxide copolymer glycol, tetrahydrofuran-ethylene oxide copolymer glycol;
[0090] According to a specific embodiment of the present invention, the second diisocyanate includes but is not limited to 4,4′-diphenylmethane diisocyanate, 2,4-diphenylmethane diisocyanate, 2,2′-diphenylmethane diisocyanate, m-xylylene diisocyanate, and 1,5-naphthalene diisocyanate.
[0091] According to a specific embodiment of the present invention, the raw materials for preparing the second polyurethane may optionally contain a second capping agent, and the second capping agent includes a monofunctional capping agent and / or a difunctional capping agent; preferably a monofunctional capping agent containing a hydroxyl group or an amino group; including but not limited to methanol, phenol, p-chlorophenol, ethanol, dibutylamine, 2-isopropylamine, isobutanol, n-butanol, amyl alcohol, isopentanol, and propanol.
[0092] According to a specific embodiment of the present invention, the first polishing layer and the second polishing layer are non-foamed bodies, thereby providing a more stable and uniform polishing effect during the polishing process.
[0093] A second aspect of the present invention provides a polishing pad, comprising a composite polishing layer and a non-woven fabric, wherein the composite polishing layer is the composite polishing layer described in the first aspect.
[0094] According to a specific embodiment of the present invention, the first polishing layer is coated on the non-woven fabric.
[0095] According to a specific embodiment of the present invention, the type of the non-woven fabric is not particularly limited, including but not limited to needle-punched non-woven fabric or spunlace non-woven fabric, such as non-woven fabric made of polypropylene, polyester, polyamide or a mixture thereof. The selected materials include but are not limited to polypropylene, polyester, nylon, viscose fiber, acrylic fiber, polyethylene fiber, chloroprene, polyester, and polyamide.
[0096] According to a specific embodiment of the present invention, the mass percentage of the composite polishing layer is not particularly limited, and as some specific examples, it is preferably 50-70%, such as 50%, 60%, 70%, etc. The mass percentage of the corresponding non-woven fabric is 30%-50%, such as 30%, 40%, 50%, etc.
[0097] The third aspect of the present invention provides a method for preparing the polishing pad according to the second aspect, comprising:
[0098] The composite polishing layer is prepared, and the composite polishing layer is composited with the non-woven fabric to obtain the polishing pad.
[0099] According to a specific embodiment of the present invention, the preparation method further comprises:
[0100] (1) A first polyether diol, a first chain extender, and a first diisocyanate are mixed to cause a first chain extension reaction to obtain a first impregnation solution.
[0101] Specifically, this step may further include: mixing a first polyether diol, a third chain extender, and a first diisocyanate to obtain a first mixed solution, wherein the molar ratio of isocyanate groups to hydroxyl groups in the first mixed solution is (1:1)-(1.5:1), and a first prepolymerization reaction occurs; adding a fourth chain extender to the mixed solution after the first prepolymerization reaction, so that the molar ratio of isocyanate groups to hydroxyl groups in the mixed solution after the first prepolymerization reaction is (0.85:1)-(1:1), a first chain extension reaction occurs, and a first impregnation solution is obtained.
[0102] Specifically, the first chain extender includes a third chain extender and a fourth chain extender, and the third chain extender and the fourth chain extender are the same or different. That is, the third chain extender and the fourth chain extender independently include at least one of a diol and a diamine; preferably an aliphatic diol and / or an aromatic diol; more preferably at least one of ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, hexanediol, neopentyl glycol, hydroquinone dihydroxyethyl ether, and resorcinol dihydroxyethyl ether.
[0103] Specifically, the molar ratio of isocyanate groups to hydroxyl groups in the first mixed solution is (1:1)-(1.5:1), such as 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, etc. The time of the first prepolymerization reaction is not particularly limited, and those skilled in the art can select it according to actual needs. As some specific examples, the time of the first prepolymerization reaction can be 1-3h, such as 1h, 2h, 3h, etc. The temperature of the first prepolymerization reaction is also not particularly limited, and is preferably 50-90°C, such as 50°C, 60°C, 70°C, 80°C, 90°C, etc.
[0104] Specifically, the molar ratio of isocyanate groups to hydroxyl groups in the mixed solution after the first prepolymerization reaction is (0.85:1)-(1:1), such as 0.85:1, 0.9:1, 0.95:1, 1:1, etc. The time of the first chain extension reaction is not particularly limited, and those skilled in the art can select it according to actual needs. As some specific examples, the time of the first chain extension reaction can be 1-3h, such as 1h, 2h, 3h, etc. The temperature of the first chain extension reaction is also not particularly limited, preferably 50-90°C, such as 50°C, 60°C, 70°C, 80°C, 90°C, etc.
[0105] Specifically, the solid content of the mixed solution after the first prepolymerization reaction is 30%-50%. As some specific examples, the solid content of the mixed solution after the first prepolymerization reaction can be 30%, 35%, 40%, 45%, 50%, etc. The solid content of the mixed solution after the first chain extension reaction is 25%-35%. As some specific examples, the solid content of the mixed solution after the first chain extension reaction is 25%, 30%, 35%, etc.
[0106] Specifically, the preparation method may further include: dissolving the first polyether diol and the third chain extender in a first solvent, and adding a first diisocyanate. The type of the first solvent is not particularly limited, and as some specific examples, at least one of N,N′-dimethylformamide (DMF), N,N′-dimethylacetamide (DMAC), or N-methylpyrrolidone (NMP) may be selected.
[0107] Specifically, the preparation method may further include: mixing the mixed solution in which the first chain extension reaction occurs with a first end-capping agent to obtain a first impregnation solution, wherein the type of the first end-capping agent is as described above.
[0108] (2) A second polyether diol, a second chain extender, and a second diisocyanate are mixed to cause a second chain extension reaction to obtain a second impregnation solution.
[0109] Specifically, this step may further include: mixing a second polyether diol and a second diisocyanate to obtain a second mixed solution, wherein the molar ratio of isocyanate groups to hydroxyl groups in the second mixed solution is (1:1)-(3:1), and a second prepolymerization reaction occurs; adding a second chain extender to the mixed solution after the second prepolymerization reaction, so that the molar ratio of isocyanate groups to hydroxyl groups in the mixed solution after the second prepolymerization reaction is (0.85:1)-(1:1), a second chain extension reaction occurs, and a second impregnation solution is obtained.
[0110] Specifically, the molar ratio of isocyanate groups to hydroxyl groups in the second mixed solution is (1:1)-(3:1), such as 1:1, 1.5:1, 2:1, 2.5:1, 3:1, etc. The time of the second prepolymerization reaction is not particularly limited, and those skilled in the art can select it according to actual needs. As some specific examples, the time of the second prepolymerization reaction can be 1-8h, such as 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, etc. The temperature of the second prepolymerization reaction is also not particularly limited, and is preferably 50-90°C, such as 50°C, 60°C, 70°C, 80°C, 90°C, etc.
[0111] Specifically, the molar ratio of isocyanate groups to hydroxyl groups in the mixed solution after the second prepolymerization reaction is (0.85:1)-(1:1), such as 0.85:1, 0.9:1, 0.95:1, 1:1, etc. The time of the second chain extension reaction is not particularly limited, and those skilled in the art can select it according to actual needs. As some specific examples, the time of the second chain extension reaction can be 1-5h, such as 1h, 2h, 3h, 4h, 5h, etc. The temperature of the second chain extension reaction is also not particularly limited, preferably 50-90°C, such as 50°C, 60°C, 70°C, 80°C, 90°C, etc.
[0112] Specifically, the solid content of the mixed solution after the second prepolymerization reaction is 30%-50%. As some specific examples, the solid content of the mixed solution after the second prepolymerization reaction can be 30%, 35%, 40%, 45%, 50%, etc. The solid content of the mixed solution after the second chain extension reaction is 25%-35%. As some specific examples, the solid content of the mixed solution after the second chain extension reaction is 25%, 30%, 35%, etc.
[0113] Specifically, the preparation method may further include: dissolving the second polyether diol in a second solvent, and adding a second diisocyanate. The type of the second solvent is not particularly limited, and as some specific examples, at least one of N,N′-dimethylformamide (DMF), N,N′-dimethylacetamide (DMAC), or N-methylpyrrolidone (NMP) may be selected.
[0114] Specifically, the preparation method may further include: mixing the mixed solution in which the second chain extension reaction occurs with a second end-capping agent to obtain a second impregnation solution, wherein the type of the second end-capping agent is as described above.
[0115] (3) Immersing the nonwoven fabric in the first impregnating liquid and performing a first heat treatment to obtain a nonwoven fabric covered with a first polishing layer.
[0116] Specifically, the preparation method may further include: diluting the first impregnation liquid, and then immersing the non-woven fabric in the first impregnation liquid. The first impregnation liquid may be diluted to 8%-20%, such as 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, etc., thereby achieving better wettability.
[0117] Specifically, the nonwoven fabric is immersed in the first impregnation liquid, and after being completely impregnated, the excess impregnation liquid on the upper and lower surfaces is scraped off, and then heat treatment is performed. At the same time, the impregnation process can be carried out under pressure, and the pressure condition can be achieved by vacuuming. The vacuuming time can be 0-10s, and the vacuum degree is 0-0.9MPa.
[0118] Specifically, the temperature and time of the first heat treatment are not particularly limited, and the drying of the solvent can be achieved, for example, treatment at 150-180° C. for 0.1-1 h.
[0119] (4) Immersing the nonwoven fabric covered with the first polishing layer in the second impregnating liquid and performing a second heat treatment to obtain the polishing pad.
[0120] Specifically, the preparation method may further include: diluting the second impregnating liquid, and then immersing the non-woven fabric coated with the first polishing layer in the second impregnating liquid. The second impregnating liquid may be diluted to 8%-20%, such as 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, etc., to achieve better wettability.
[0121] Specifically, the nonwoven fabric coated with the first polishing layer is immersed in the second impregnation liquid, and after being completely impregnated, the excess impregnation liquid on the upper and lower surfaces is scraped off, and then heat treatment is performed. At the same time, the impregnation process can be carried out under pressure, and the pressure condition can be achieved by vacuuming. The vacuuming time can be 0-10s, and the vacuum degree is 0-0.9MPa.
[0122] Specifically, the temperature and time of the second heat treatment are not particularly limited, and the solvent can be dried, for example, at 150-180° C. for 0.1-1 h. In addition, after the second heat treatment, conventional grinding, grooving, cutting, adhesive backing operations, etc. can be performed to obtain the polishing pad.
[0123] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.
[0124] Example 1
[0125] The composition and weight percentage of the polishing pad prepared in this embodiment are as follows: 60% polyurethane and 40% non-woven fabric, the non-woven fabric is a needle-punched polyester non-woven fabric with a gram weight of 270 g / m 2 , the fiber diameter is 17μm and the thickness is 1.6mm.
[0126] Preparation of the first impregnation solution: polytetramethylene glycol (PTMG1000) with a molecular weight of 1000 g / mol and 1,4-butanediol are dissolved in DMF solvent at a molar ratio of 10:1; diisocyanate is added dropwise, which is a mixture of 2,4-MDI and 4,4′-MDI, the molar ratio of isocyanate group to alcohol hydroxyl group is 1.5:1, and the solid content of the solution is 40%. After reacting for 1 hour, hydroquinone dihydroxyethyl ether and DMAC are added to make the molar ratio of alcohol hydroxyl group to isocyanate group 1:0.95, and the solid content of the solution is 30%. After reacting for 1.5 hours, methanol is added for end-capping for 1.5 hours, and the reaction temperature is 70°C throughout the process;
[0127] Preparation of the second impregnation solution: dissolve polytetramethylene glycol (PTMG2000) with a molecular weight of 2000 g / mol in DMAC solvent, add diisocyanate dropwise, which is 4,4′-MDI, the molar ratio of alcohol hydroxyl group to isocyanate group is 1:1.5, the solid content of the solution is 40%, react at 65°C for 2h, add polyethylene glycol (PEG 600), the molar ratio of alcohol hydroxyl group to isocyanate group is 1:0.9, heat to 80°C, the solid content of the solution is 30%, and react for 3h;
[0128] The first impregnation liquid was diluted to 8% with DMF solvent, the non-woven fabric was spread on a flat glass plate, the first impregnation liquid was poured on the surface, and after it was completely soaked, the excess impregnation liquid on the upper and lower surfaces was scraped off, and the non-woven fabric was placed in a 100° C. oven for drying for 60 minutes, and then a flat glass plate was pressed on the upper surface, the temperature was raised to 180° C. and then treated for 10 minutes to obtain a first polishing layer;
[0129] The second impregnation liquid was diluted to 15% with NMP solvent and poured on the surface of the first polishing layer. After being squeezed with a roller until the impregnation liquid was completely soaked, excess impregnation liquid on the upper and lower surfaces was scraped off and placed in an oven at 120°C for 80 minutes. Then, conventional grinding, grooving, cutting, and back gluing operations were performed to obtain a polishing pad.
[0130] Example 2
[0131] The composition and weight percentage of the polishing pad prepared in this embodiment are as follows: 50% polyurethane and 50% non-woven fabric, the non-woven fabric is a spunlace polyester non-woven fabric with a gram weight of 300g / m 2 , the fiber diameter is 16μm and the thickness is 1.9mm.
[0132] Preparation of the first impregnation solution: polyethylene glycol (PEG200) with a molecular weight of 200 g / mol and hexylene glycol are added to a DMAC solvent in a molar ratio of 20:1; a diisocyanate is added dropwise, which is a mixture of 2,4-MDI and 4,4′-MDI, the molar ratio of isocyanate groups to alcoholic hydroxyl groups is 1.06:1, and the solid content of the solution is 35%. After reacting for 3 hours, resorcinol dihydroxyethyl ether and DMF are added to make the molar ratio of alcoholic hydroxyl groups to isocyanate groups 0.99:1, the solid content of the solution is 30%, and the reaction is carried out for 2 hours. The reaction temperature is 60°C throughout the process;
[0133] Preparation of the second impregnation solution: PTMG with a molecular weight of 1400 g / mol was put into a DMF solvent, and a diisocyanate was added dropwise, which was 4,4′-MDI, the molar ratio of alcohol hydroxyl group to isocyanate group was 1:2, and the solid content of the solution was 30%. After reacting at 80°C for 1 hour, tetrahydrofuran-propylene oxide copolymer diol and DMF were added, and the molar ratio of alcohol hydroxyl group to isocyanate group was 1:0.97, and the solid content of the solution was 30%. The temperature was raised to 85°C for reaction for 3 hours;
[0134] The first impregnation liquid was diluted to 10% with DMF solvent, and the non-woven fabric was spread on a flat marble adsorption platform, and the first impregnation liquid was poured on the surface, and the vacuum was turned on. After no liquid remained on the upper layer, the excess impregnation liquid on the lower surface was scraped off, and the surface was placed in an oven at 105° C. and dried for 70 minutes. Subsequently, a flat glass plate was pressed on the upper surface, and the temperature was raised to 150° C. and treated for another 60 minutes to obtain a first polishing layer;
[0135] The second impregnation liquid was diluted to 8% with NMP solvent and poured on the surface of the first polishing layer. After being squeezed with a roller until the impregnation liquid was completely soaked, excess impregnation liquid on the upper and lower surfaces was scraped off and placed in an oven at 120°C for 80 minutes. Then, conventional grinding, grooving, cutting, and back gluing operations were performed to obtain a polishing pad.
[0136] Example 3
[0137] The composition and weight percentage of the polishing pad prepared in this embodiment are as follows: 70% polyurethane and 30% non-woven fabric, the non-woven fabric is a needle-punched polyester non-woven fabric with a gram weight of 220g / m 2 , the fiber diameter is 20μm and the thickness is 1.7mm.
[0138] Preparation of the first impregnation solution: polytetramethylene glycol ether (PTMG 250) with a molecular weight of 250 g / mol and resorcinol dihydroxy ether are added to a DMAC solvent at a molar ratio of 12:1; a diisocyanate is added dropwise, which is a mixture of 2,4-MDI and 4,4′-MDI, the molar ratio of isocyanate groups to alcoholic hydroxyl groups is 1.3:1, and the solid content of the solution is 37%. After reacting for 2 hours, ethylene glycol and NMP are added to make the molar ratio of alcoholic hydroxyl groups to isocyanate groups 1:0.95, the solid content of the solution is 30%, and the reaction is carried out for 1.5 hours. The reaction temperature is 55°C throughout the process;
[0139] Preparation of the second impregnation solution: The reaction temperature is 90°C throughout the process, PTMG with a molecular weight of 1200 g / mol is put into DMF solvent, and diisocyanate is added dropwise, which is a mixture of 2,4-MDI and 4,4′-MDI, the molar ratio of alcohol hydroxyl group to isocyanate group is 1:1.2, and the solid content of the solution is 45%. After reacting for 2 hours, polyethylene glycol (PEG 1000) and NMP are added, and the molar ratio of alcohol hydroxyl group to isocyanate group is 1:0.99, and the solid content of the solution is 30%. After reacting for 2 hours, methanol is added and the temperature is reduced to 60°C and the reaction is continued for 0.5 hours;
[0140] The first impregnation liquid was diluted to 18% with DMAC solvent, the non-woven fabric was spread on a flat glass plate, the first impregnation liquid was poured on the surface, and after it was completely soaked, the excess impregnation liquid on the upper and lower surfaces was scraped off, and the non-woven fabric was placed in a 100° C. oven for drying for 60 minutes, and then a flat glass plate was pressed on the upper surface, the temperature was raised to 170° C. and then treated for 30 minutes to obtain a first polishing layer;
[0141] The second impregnation liquid was diluted to 11% with NMP solvent and poured on the surface of the first polishing layer. After being squeezed with a roller until the impregnation liquid was completely soaked, excess impregnation liquid on the upper and lower surfaces was scraped off and placed in an oven at 120°C for 80 minutes. Then, conventional grinding, grooving, cutting, and back gluing operations were performed to obtain a polishing pad.
[0142] Example 4
[0143] The composition and weight percentage of the polishing pad prepared in this embodiment are as follows: 55% polyurethane and 45% non-woven fabric, the non-woven fabric is a needle-punched polyester non-woven fabric with a gram weight of 220g / m 2 , the fiber diameter is 20μm / 14μm and the thickness is 1.7mm.
[0144] Preparation of the first impregnation solution: bisphenol A polyoxyethylene ether and neopentyl glycol are added to DMF solvent in a molar ratio of 25:1; diisocyanate is added dropwise, which is 4,4′-MDI, the molar ratio of isocyanate group to alcohol hydroxyl group is 1.05:1, and the solid content of the solution is 35%. After reacting for 2 hours, 1,4-butanediol and DMF are added to make the molar ratio of alcohol hydroxyl group to isocyanate group 1:1, and the solid content of the solution is 30%. After reacting for 1.5 hours, isobutanol is added and reacted for another 1 hour, and the reaction temperature is 70°C throughout the process;
[0145] Preparation of the second impregnation solution: PTMG with a molecular weight of 1200 g / mol was put into DMF solvent, and diisocyanate was added dropwise, which was a mixture of 2,4-MDI and 4,4′-MDI, the molar ratio of alcohol hydroxyl group to isocyanate group was 1:1.2, and the solid content of the solution was 45%. After reacting at 85°C for 2 hours, polypropylene glycol (PPG 600) and NMP were added, and the molar ratio of alcohol hydroxyl group to isocyanate group was 0.99:1, and the solid content of the solution was 30%. After the temperature was raised to 90°C for reaction for 2 hours, ethanol was added and the temperature was lowered to 65°C and the reaction was continued for 0.5 hours;
[0146] The first impregnation liquid was diluted to 9% with DMAC solvent, the non-woven fabric was spread on an aluminum vacuum adsorption platform, the first impregnation liquid was poured on the surface, the vacuum was turned on, the impregnation liquid was completely soaked in the non-woven fabric, the excess impregnation liquid on the upper and lower surfaces was scraped off, and the non-woven fabric was placed in a 100° C. oven for drying for 60 minutes, and then a flat glass plate was pressed on the upper surface, the temperature was raised to 160° C. and then treated for 20 minutes to obtain a first polishing layer;
[0147] The second impregnation liquid was diluted to 12% with NMP solvent and poured on the surface of the first polishing layer. After being squeezed with a roller until the impregnation liquid was completely soaked, excess impregnation liquid on the upper and lower surfaces was scraped off and placed in an oven at 120°C for 80 minutes. Then, conventional grinding, grooving, cutting, and back gluing operations were performed to obtain a polishing pad.
[0148] Comparative Example 1
[0149] The components and weight percentages of the polishing pad prepared in this comparative example are as follows: 60% polyurethane and 40% non-woven fabric.
[0150] Preparation of the impregnation solution: polytetramethylene glycol ether (PTMG 650) and ethylene glycol are added to a DMF solvent at a molar ratio of 13:1; a diisocyanate is added dropwise, which is NDI, the molar ratio of isocyanate groups to alcoholic hydroxyl groups is 1.15:1, and the solid content of the solution is 32%. After reacting for 2 hours, ethylene glycol and DMF are added to make the molar ratio of alcoholic hydroxyl groups to isocyanate groups 1:0.96, and the solid content of the solution is 28%, and the reaction is continued for 2 hours;
[0151] The impregnation liquid was diluted to 20% with DMAC solvent, the non-woven fabric was spread on a flat glass plate, the impregnation liquid was poured on the surface, and after it was completely soaked, the excess impregnation liquid on the upper and lower surfaces was scraped off, and it was sent to a 100°C oven for drying for 90 minutes. Subsequently, a flat glass plate was pressed on the upper surface, the temperature was raised to 150°C and treated for another 10 minutes, and then conventional grinding, grooving, cutting, and back-gluing operations were performed to obtain a polishing pad.
[0152] Comparative Example 2
[0153] The components and weight percentages of the polishing pad prepared in this comparative example are as follows: 60% polyurethane and 40% non-woven fabric.
[0154] Preparation of impregnation solution: PTMG with a molecular weight of 1800 g / mol was put into DMF solvent, and diisocyanate was added dropwise, which was a mixture of 2,4-MDI, 4,4′-MDI and NDI, the molar ratio of alcohol hydroxyl group to isocyanate group was 1:1.1, and the solid content of the solution was 40%. After reacting for 2 hours, polyethylene glycol (PEG 2000) and NMP were added, and the molar ratio of alcohol hydroxyl group to isocyanate group was 0.98:1, the solid content of the solution was 25%, and the reaction was carried out for 3 hours.
[0155] The impregnation liquid was diluted to 19% with DMF solvent, the non-woven fabric was spread on a flat glass plate, the impregnation liquid was poured on the surface, and after it was completely soaked, the excess impregnation liquid on the upper and lower surfaces was scraped off, and it was placed in a 100°C oven for drying for 90 minutes. Subsequently, a flat glass plate was pressed on the upper surface, the temperature was raised to 175°C and then treated for another 10 minutes, and then conventional grinding, grooving, cutting, and back gluing operations were performed to obtain a polishing pad.
[0156] Comparative Example 3
[0157] The components and weight percentages of the polishing pad prepared in this comparative example are as follows: 60% polyurethane and 40% non-woven fabric.
[0158] Preparation of the first impregnation solution: TPU-50A (commercially available conventional material, hardness ≥ 50A) was added to the DMF solvent in batches, and stirred at 60°C until completely dissolved, and the solid content of the solution was 11%;
[0159] Preparation of the second impregnation solution: TPU-95A (commercially available conventional material, hardness ≥ 95A) was added to the NMP solvent in batches, and stirred at 60°C until completely dissolved, and the solid content of the solution was 11%;
[0160] The non-woven fabric is spread on a flat glass plate, and the first impregnation liquid is poured on the surface. After it is completely soaked, the excess impregnation liquid on the upper and lower surfaces is scraped off, and the non-woven fabric is placed in a 120°C oven for drying for 60 minutes. Subsequently, a flat glass plate is pressed on the upper surface, and the temperature is raised to 160°C for further treatment for 20 minutes to obtain the first polishing layer;
[0161] Place the first polishing layer on an aluminum alloy adsorption platform, pour the second impregnation liquid on the surface, turn on the vacuum until the lower layer of liquid is completely soaked, scrape off the excess impregnation liquid on the lower surface, put it into a 120°C oven to dry for 70 minutes, and then perform conventional grinding, grooving, cutting, and gluing operations to obtain a polishing pad.
[0162] Test Case
[0163] (1) Wafer polishing test
[0164] After grinding, groove engraving and gluing the polishing pad, the pad was placed on a chemical mechanical polisher to continuously polish the carbon or silicon surface of a 6-inch silicon carbide wafer for 2 hours. The thickness removal per unit time of each surface of the wafer was measured, which was the removal rate.
[0165] The polishing pad surface is considered to have failed when obvious fuzzing occurs or multiple through scratches appear on the SiC wafer surface. The polishing time from the start of polishing to the occurrence of obvious fuzzing is considered to be the life of the polishing layer.
[0166] (2) Wafer surface testing
[0167] A three-dimensional white light profilometer is used to test each surface of the wafer before and after polishing;
[0168] (3) Polishing layer hardness test
[0169] Refer to GB / T2411-2008 "Determination of indentation hardness (Shore hardness) of plastics and hard rubber using a hardness tester", stack several layers of samples to make the test thickness greater than 4mm, and use a Shore A hardness tester to test the hardness of five points of the sample and take the average value;
[0170] (4) Polyurethane hard segment content test
[0171] The polyurethane hard segment content is tested by nuclear magnetic resonance testing or Fourier transform infrared spectroscopy;
[0172] (5) Polishing layer compression test
[0173] Refer to GB / T 24442.1-2009 "Determination of compression properties of textiles Part 1: Constant method" test, first grind the polishing layer, set the constant pressure to 8N, raise the temperature from room temperature to 75℃, remove the pressure and return to room temperature, measure the initial thickness, thickness during the test, and thickness at the end of the test, and get the compression rate and rebound rate;
[0174] (6) Micromorphology test
[0175] The surface and cross-sectional micromorphology of the polishing layer were tested by field emission scanning electron microscopy.
[0176] in Figure 1-7 The surface and cross-sectional micromorphology of the polishing layer. Figure 1 It can be seen that Figure 2 The surface is obviously coated with resin.
[0177] Figure 8-9 The following are the test results of each surface of the wafer before and after polishing using a 3D white light profilometer. Figure 8 The middle wafer showed a water-rippled surface with a height difference of 882nm, indicating that only chemical action was performed and the mechanical removal effect was poor; Fig. 9 It shows that the surface of the polished wafer in Comparative Example 1 has scratches running through it.
[0178] The remaining test results are shown in the table below. The results show that, compared with the comparative example, the polishing layer prepared by the method provided by the present invention has a high wafer removal rate, and the polishing pad has a longer service life.
[0179] Table 1
[0180]
[0181] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0182] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A composite polishing layer, characterized in that: The composite polishing layer comprises a first polishing layer and a second polishing layer, wherein the second polishing layer is coated on the first polishing layer; Wherein, the first polishing layer comprises a first polyurethane, the hardness of the first polyurethane is 95-110A, and the number average molecular weight is 3w-5w g / mol; The second polishing layer includes a second polyurethane, and the hardness of the second polyurethane is 50-70A and the number average molecular weight is 5w-20w g / mol.
2. The composite polishing layer according to claim 1, characterized in that: The first polyurethane is a reaction product comprising a first polyether diol, a first chain extender, a first diisocyanate, and an optional first end-capping agent; Wherein, the number average molecular weight of the first polyether diol is 200-1000 g / mol; and / or, the hard segment content in the first polyurethane is 45-75wt%; And / or, the first polyether diol includes at least one of polytetramethylene glycol, polyethylene glycol, polypropylene glycol, tetramethylene glycol-propylene oxide copolymer, propylene oxide-ethylene oxide copolymer, bisphenol A polyoxyethylene ether, and bisphenol A polyoxypropylene ether; And / or, the first chain extender comprises at least one of a diol and a diamine; preferably an aliphatic diol and / or an aromatic diol; more preferably at least one of ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, hexanediol, neopentyl glycol, hydroquinone dihydroxyethyl ether, and resorcinol dihydroxyethyl ether; and / or, the first diisocyanate includes at least one of 4,4′-diphenylmethane diisocyanate, 2,4-diphenylmethane diisocyanate, 2,2′-diphenylmethane diisocyanate, m-xylylene diisocyanate, and 1,5-naphthalene diisocyanate; And / or, the first capping agent includes a monofunctional capping agent and / or a difunctional capping agent; preferably a monofunctional capping agent containing a hydroxyl group or an amino group; more preferably at least one of methanol, phenol, p-chlorophenol, ethanol, dibutylamine, 2-isopropylamine, isobutanol, n-butanol, amyl alcohol, isopentanol, and propanol.
3. The composite polishing layer according to claim 1, characterized in that: The second polyurethane is a reaction product comprising a second polyether diol, a second chain extender, a second diisocyanate, and an optional second end-capping agent; Wherein, the number average molecular weight of the second polyether diol is 200-3000 g / mol; And / or, the hard segment content in the second polyurethane is 5-40wt%; And / or, the second polyether diol comprises at least one of polytetramethylene ether diol and a polyether diol using bisphenol A as an initiator; And / or, the polyether diol using bisphenol A as an initiator includes but is not limited to at least one of bisphenol A polyoxyethylene ether and bisphenol A polyoxypropylene ether; and / or, the molecular weight of the second chain extender is 500-2000 g / mol; preferably at least one of polyethylene glycol, polypropylene glycol, tetrahydrofuran-propylene oxide copolymer glycol, and tetrahydrofuran-ethylene oxide copolymer glycol; and / or, the second diisocyanate comprises at least one of 4,4′-diphenylmethane diisocyanate, 2,4-diphenylmethane diisocyanate, 2,2′-diphenylmethane diisocyanate, m-xylylene diisocyanate, and 1,5-naphthalene diisocyanate; And / or, the second capping agent includes a monofunctional capping agent and / or a difunctional capping agent; preferably a monofunctional capping agent containing a hydroxyl group or an amino group; more preferably at least one of methanol, phenol, p-chlorophenol, ethanol, dibutylamine, 2-isopropylamine, isobutanol, n-butanol, amyl alcohol, isopentanol, and propanol.
4. The composite polishing layer according to claim 1, characterized in that: The first polishing layer and the second polishing layer are non-foamed bodies.
5. A polishing pad, characterized in that: The invention comprises a composite polishing layer and a non-woven fabric, wherein the composite polishing layer is the composite polishing layer according to any one of claims 1 to 4.
6. The polishing pad according to claim 5, characterized in that The first polishing layer is coated on the non-woven fabric; And / or, the composite polishing layer in the polishing pad accounts for 50%-70% by mass, and the non-woven fabric accounts for 30%-50% by mass.
7. A method for preparing a polishing pad according to claim 5 or 6, characterized in that: include: The composite polishing layer is prepared, and the composite polishing layer is composited with the non-woven fabric to obtain the polishing pad.
8. The preparation method according to claim 7, characterized in that: The preparation method further comprises: The first polyether diol, the first chain extender, and the first diisocyanate are mixed to generate a first chain extension reaction to obtain a first impregnation solution; The second polyether diol, the second chain extender and the second diisocyanate are mixed to generate a second chain extension reaction to obtain a second impregnation solution; Immersing the nonwoven fabric in the first impregnation liquid and performing a first heat treatment to obtain a nonwoven fabric coated with a first polishing layer to obtain a first polishing layer; The nonwoven fabric covered with the first polishing layer is immersed in the second impregnating liquid and subjected to a second heat treatment to obtain the polishing pad.
9. The preparation method according to claim 8, characterized in that: The preparation method further comprises: The first polyether diol, the third chain extender, and the first diisocyanate are mixed to obtain a first mixed solution, wherein the molar ratio of isocyanate groups to hydroxyl groups in the first mixed solution is (1:1)-(1.5:1), and a first prepolymerization reaction occurs; the fourth chain extender is added to the mixed solution after the first prepolymerization reaction, so that the molar ratio of isocyanate groups to hydroxyl groups in the mixed solution after the first prepolymerization reaction is (0.85:1)-(1:1), and a first chain extension reaction occurs to obtain a first impregnation solution; A second polyether diol and a second diisocyanate are mixed to obtain a second mixed solution, wherein the molar ratio of isocyanate groups to hydroxyl groups in the second mixed solution is (1:1)-(3:1), and a second prepolymerization reaction occurs; a second chain extender is added to the mixed solution after the second prepolymerization reaction, such that the molar ratio of isocyanate groups to hydroxyl groups in the mixed solution after the second prepolymerization reaction is (0.85:1)-(1:1), and a second chain extension reaction occurs to obtain a second impregnation solution; Wherein, the first chain extender includes a third chain extender and a fourth chain extender, and the third chain extender and the fourth chain extender are the same or different.
10. The preparation method according to claim 9, characterized in that: The solid content of the mixed solution after the first prepolymerization reaction is 30%-50%; and / or, the solid content of the mixed solution after the first chain extension reaction is 25%-35%; and / or, the solid content of the mixed solution after the second prepolymerization reaction is 30%-50%; And / or, the solid content of the mixed solution after the second chain extension reaction is 25%-35%.
11. The preparation method according to any one of claims 8 to 10, characterized in that: The preparation method further comprises: Diluting the first impregnation solution to a solid content of 8% to 20%; And / or, the second impregnation liquid is diluted to have a solid content of 8%-20%.
12. The preparation method according to any one of claims 9 to 11, characterized in that: The first prepolymerization reaction time is 1-3h; and / or, the temperature of the first prepolymerization reaction is 50-90° C.; And / or, the time of the first chain extension reaction is 1-3h; And / or, the temperature of the first chain extension reaction is 50-90°C.
13. The preparation method according to any one of claims 9 to 11, characterized in that: The second prepolymerization reaction time is 1-8h; and / or, the temperature of the second prepolymerization reaction is 50-90° C.; And / or, the time of the second chain extension reaction is 1-5h; And / or, the temperature of the second chain extension reaction is 50-90°C.
14. The preparation method according to any one of claims 8 to 13, characterized in that: The preparation method further comprises: mixing the mixed solution after the first chain extension reaction with the first end-capping agent to obtain a first impregnation solution; And / or, the mixed solution after the second chain extension reaction is mixed with the second end-capping agent to obtain a second impregnation solution.
Citation Information
Patent Citations
Conductive polishing pad and manufacturing method thereof
CN101780661A
Multilayer Chemical Mechanical Polishing Pad Stack With Soft And Conditionable Polishing Layer
CN104209874A
Polishing pad
CN115284166A
Polishing pad base material and preparation method thereof
CN117924644A
Polishing pad, polishing device, and polishing method using the same
JP2002079456A
Cited By
Polishing pad and preparation method and application thereof
CN121870630A
A polishing pad and its preparation method and application
CN121870630B